PLGA-corosolic acid implants for potential application in ocular neovascularization diseases - Cibele Rodrigues Toledo; Vinícius Viana Pereira; Gracielle Ferreira Andrade; Armando Silva-Cunha (Universidade de São Paulo, 2020)
Angiogenesis is the formation of new blood vessels from preexisting vasculature. Uncontrolled angiogenesis is associated with progression of several ocular pathologies, such as diabetic retinopathy and macular degeneration. Thus, the inhibition of this process consists in an interesting therapeutic target. Corosolic acid (CA) is a natural derivative of ursolic acid, found in many medicinal herbs and exhibits numerous biological properties, including the antiangiogenic activity. The present study reports the production of CA-loaded poly d,l-lactidecoglycolide acid (PLGA) devices by melt technique. HPLC-UV method was developed and validated to evaluate the uniformity and the release profile of the developed systems. The devices were also characterized by Fourier transform infrared spectroscopy, thermal analysis, and scanning electron morphology. It was studied the antiangiogenic activity of the CA-polymer system, using an in vivo model, the chorioallantoic membrane assay (CAM). CA was dispersed uniformly in the polymer matrix and no chemical interaction between the components of the formulation was verified. The implants presented a sustained release of the drug, which was confirmed by the morphological study and demonstrated an antiangiogenic activity. Therefore, the developed delivery system is a promising therapeutic tool for the treatment of ocular diseases associated with neovascularization or others related to the angiogenic process.